Bridging the Gap: Structured, Sustainable Mentorship Models in Higher Learning Institutions (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Mentorship is widely recognised as a critical intervention for equipping young and early career academic staff with the skills necessary to navigate the complex demands of higher learning institutions (HLIs). However, evaluating the effectiveness of mentorship programs remains a big challenge. This article seeks to explore alternative mentorship models applicable in HLIs beyond structured programs, identify key challenges facing structured mentorship initiatives, and outline best practices for developing effective and sustainable mentorship frameworks. Using the Google Scholar database, we conducted a systematic literature review of 26 peer-reviewed journal articles published between 2015 and 2025. Findings reveal that alternative models such as traditional dyadic, peer, group, distance, and constellation mentorship are viable in HLIs. Common challenges to structured mentorship include time constraints, scheduling conflicts, heavy workloads, limited mentorship skills, insufficient institutional support, mismatched pairings, and a shortage of qualified mentors. The article highlights best practices, including comprehensive mentor training, optimal matching, time dedication, institutional backing, voluntary participation, mentor compensation, robust monitoring and evaluation mechanisms, and clearly defined learning goals. These elements are essential for building effective and sustainable structured mentorship models in HLIs.